Challenges of the training function in the promotion of human resources In Algerian public banks - Tayeb AMARA (Dirassat Journal Economic Issue, 2025)
The importance of the study in highlighting the function of training is evident in being the basis of excellence, and confirm the ability to keep pace with challenges and  even overcome them in an industry laboratory  Human resources in Algerian public banks. For this, the training function had to ensure the immediate and future results adopted in global  policies. The process of  polling the opinions of a sample consisting of (107)  central and regional frameworks specialized in human resources management, and the outputs of the statistical program (SPSS). V.21), there is a statistically significant relationship between the training function and the expected return of human resources, without statistically significant differences on the extent of the commitment of the  directors of training centers to apply curricula that enhance  the status of the training function, due to the factors of professional qualification, academic qualification, current position, seniority.